Integral of tgh^2 dx
The solution
Detail solution
-
Let u=tanh(x).
Then let du=(1−tanh2(x))dx and substitute −du:
∫(−u2−1u2)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫u2−1u2du=−∫u2−1u2du
-
Rewrite the integrand:
u2−1u2=1−2(u+1)1+2(u−1)1
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫1du=u
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−2(u+1)1)du=−2∫u+11du
-
Let u=u+1.
Then let du=du and substitute du:
∫u1du
-
The integral of u1 is log(u).
Now substitute u back in:
log(u+1)
So, the result is: −2log(u+1)
-
The integral of a constant times a function is the constant times the integral of the function:
∫2(u−1)1du=2∫u−11du
-
Let u=u−1.
Then let du=du and substitute du:
∫u1du
-
The integral of u1 is log(u).
Now substitute u back in:
log(u−1)
So, the result is: 2log(u−1)
The result is: u+2log(u−1)−2log(u+1)
So, the result is: −u−2log(u−1)+2log(u+1)
Now substitute u back in:
−2log(tanh(x)−1)+2log(tanh(x)+1)−tanh(x)
-
Add the constant of integration:
−2log(tanh(x)−1)+2log(tanh(x)+1)−tanh(x)+constant
The answer is:
−2log(tanh(x)−1)+2log(tanh(x)+1)−tanh(x)+constant
The answer (Indefinite)
[src]
/
|
| 2 log(1 + tanh(x)) log(-1 + tanh(x))
| tanh (x) dx = C + ---------------- - tanh(x) - -----------------
| 2 2
/
∫tanh2(x)dx=C−2log(tanh(x)−1)+2log(tanh(x)+1)−tanh(x)
The graph
1−tanh(1)
=
1−tanh(1)
Use the examples entering the upper and lower limits of integration.